Between Enslavement and Liberation. Narratives of Belonging from Two Farm Workers in Rural South Africa - Coetzee, Jan K.; Rau, Asta (Qualitative Sociology Review, 2017)
More than two decades after the genesis of South Africa’s aspirational democracy in 1994, deep-seated forms of inequality still exist. These are explored in the narratives of two farm workers who tell of events and experiences in their everyday lives. In probing the everyday, we turn the spotlight on phenomena, events, and experiences that are simultaneously familiar yet perplexing, taken-for-granted yet questionable, tangible yet elusive. As a backdrop to the sociology of the everyday, key ideas from three social theorists — Randall Collins, Jeffrey Alexander, and Vanessa May — guide our interpretation of excerpts from the farm workers’ narratives. The farm workers’ stories are also juxtaposed with reflections on the socio-political, economic, and emotional contexts of slavery and serfdom.